Emotions as a Multi-Modal System of Representation in Non-Linguistic Thinking - Dieter Lohmar (Rosenberg & Sellier, 2017)
Emotions can carry meaning, evaluations, knowledge, experience and sometimes also plans for the future, thus they can function as part of non-linguistic thinking. In my contribution I would like to establish the function of emotions as an important part of an effective system of thinking and deciding that does not use the concepts of language but visual scenes combined with feelings.